Social Vitality and Its Influencing Factors (Case Study: Primary Schools in Behshahr) - Parichehreh Teroujeni, Morteza; Sotodehasl, Nemat; Makvand Hosseini, Shahrokh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to investigate the components and influencing factors of social vitality among primary school students in Behshahr through a mixed-methods exploratory approach. Methods and Materials: The research employed a sequential exploratory mixed-methods design consisting of qualitative and quantitative phases. In the qualitative phase, semi-structured interviews were conducted with primary school teachers and administrators to identify key components of social vitality. Thematic analysis was applied to extract codes, which were then refined through Delphi rounds and expert consultation. These findings informed the development of a 90-item researcher-made questionnaire. In the quantitative phase, data were collected from a statistically representative sample using Cochran’s formula, and exploratory factor analysis was conducted to identify underlying factors. Findings: Exploratory factor analysis revealed eight key factors influencing social vitality among students: environmental, teacher, perception and motivation of joy, socio-cultural, interpersonal relationships, art and aesthetics, health and well-being, and management. Together, these factors explained 27.4% of the variance in students’ social vitality. Among them, the environmental factor had the highest explanatory power. The final model integrated 90 variables across these eight dimensions, validated through both statistical and qualitative methods. Conclusion: The findings emphasize the multidimensional nature of social vitality in educational settings, highlighting the significance of school infrastructure, teacher-student relationships, emotional motivation, and leadership practices. Schools that adopt holistic strategies targeting these areas can better foster emotional well-being, engagement, and a sense of belonging among students. The study also contributes a validated model for assessing and enhancing social vitality in primary education within the Iranian context.